An Analysis of the Role of Human Resource Management in Enhancing Organizational Efficiency and Effectiveness - Natsir, Imron; Ode, Haruni; Irfana, Tungga Buana; Pulungan, Delyana Rahmawany; Sihite, Mislan (International Journal of Economics (IJEC), 2024)
The objective of this research is to examine the impact of human resource management (HRM) on the efficiency and effectiveness of organizational operations. This research employs a literature review methodology, encompassing the examination of a multitude of pertinent academic sources, journals, and articles. The findings of this study indicate that effective human resource management, as evidenced by recruitment practices, training, employee development, and performance evaluation, can markedly enhance operational efficiency and organizational effectiveness. Moreover, factors such as job satisfaction, motivation, and organizational culture also exert a significant influence on the attainment of organizational objectives. Consequently, strategic human resource management represents a pivotal determinant of organizational success in the context of global competition.